2015
DOI: 10.1080/15374416.2015.1030752
|View full text |Cite
|
Sign up to set email alerts
|

Parenting as a Moderator of the Effects of Maternal Depressive Symptoms on Preadolescent Adjustment

Abstract: Objective The purpose of this study was to examine whether parenting moderated the association between maternal depressive symptoms and initial levels and growth of preadolescent internalizing and externalizing symptoms. Method This study used a community sample of pre-adolescent children (N=214; 8–12 years old at Time 1), measuring maternal depressive symptoms and parenting at Time 1, and preadolescent internalizing and externalizing symptoms at each year for 3 years. Results After modeling latent growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
27
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 49 publications
6
27
0
2
Order By: Relevance
“…Positive parenting practices are a protective factor and promote child social skills (Rovaris & Bolsoni-Silva, 2018), a piece of information corroborated here; these variables appear correlated in this study. As expected, negative parenting practices were strongly associated with reports of behavioral problems, an association that was identified in both groups, regardless of the presence of maternal depression, which agrees with the findings reported by other studies (Dow-Fleisner, 2018;Silk et al, 2011;Pizeta et al, 2013;Rovaris & Bolsoni-Silva, 2018;Trepat et al, 2014;Vafaeenejad et al, 2018;Zalewski et al, 2017). Note, however, that the scores concerning the indicators of depression obtained by the sample of mothers with indicators of depression were not associated with the indicators of children's behaviors, which seems to disagree with the literature (Conners-Burrow et al, 2016;Pizeta et al, 2013;Silk et al, 2011;Trepat et al, 2014;Zalewski et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Positive parenting practices are a protective factor and promote child social skills (Rovaris & Bolsoni-Silva, 2018), a piece of information corroborated here; these variables appear correlated in this study. As expected, negative parenting practices were strongly associated with reports of behavioral problems, an association that was identified in both groups, regardless of the presence of maternal depression, which agrees with the findings reported by other studies (Dow-Fleisner, 2018;Silk et al, 2011;Pizeta et al, 2013;Rovaris & Bolsoni-Silva, 2018;Trepat et al, 2014;Vafaeenejad et al, 2018;Zalewski et al, 2017). Note, however, that the scores concerning the indicators of depression obtained by the sample of mothers with indicators of depression were not associated with the indicators of children's behaviors, which seems to disagree with the literature (Conners-Burrow et al, 2016;Pizeta et al, 2013;Silk et al, 2011;Trepat et al, 2014;Zalewski et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…As expected, negative parenting practices were strongly associated with reports of behavioral problems, an association that was identified in both groups, regardless of the presence of maternal depression, which agrees with the findings reported by other studies (Dow-Fleisner, 2018;Silk et al, 2011;Pizeta et al, 2013;Rovaris & Bolsoni-Silva, 2018;Trepat et al, 2014;Vafaeenejad et al, 2018;Zalewski et al, 2017). Note, however, that the scores concerning the indicators of depression obtained by the sample of mothers with indicators of depression were not associated with the indicators of children's behaviors, which seems to disagree with the literature (Conners-Burrow et al, 2016;Pizeta et al, 2013;Silk et al, 2011;Trepat et al, 2014;Zalewski et al, 2017). In the total sample, maternal depression was inversely proportional to positive practices (Dow-Fleisner, 2018;Silk et al, 2011;Pizeta et al, 2013;Trepat et al, 2014;Vafaeenejad et al, 2018;Zalewski et al, 2017) and directly related to children's social skills Table 4 Simple linear regression analysis with only externalizing behavior problems as the dependent variable (n = 13, and nonclinical-n = 21) and the following independent variables: maternal depression, positive parenting practices, negative parenting practices, quality of marital relationship, children's social skills, and mothers' reports of problems Table 5 Simple linear regression analysis with internalizing and externalizing comorbidities as the dependent variable (n = 13, and non-clinical-n = 21) and the following independent variables: maternal depression, positive parenting practices, negative parenting practices, quality of marital relationship, children's social skills, and mothers' reports of problems (Rovaris & Bolsoni-Silva, 2018), which in turn were inversely proportional to indicators of behavioral problems (Rovaris & Bolsoni-Silva, 2018).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Supplementing this relatively limited literature on cumulative risk and parenting are a number of studies that have found parenting to moderate other specific risk exposures that also threaten children's well-being. In terms of exacerbating factors, harsh or rejecting parenting and family conflict have been shown to moderate the relation between parents' and children's mental health outcomes (Conners-Burrow et al, 2013;Zalewski, Thompson, & Lengua, 2017). On the other hand, several studies have documented protective effects of positive parenting in contexts of violence exposure and abuse (Afifi & MacMillan, 2011;Corbett, 2013;Garrido & Taussig, 2013).…”
Section: Evidence For Parenting Moderating Riskmentioning
confidence: 99%